Analisis Kompetensi Numerasi Siswa Kelas V di SDN Gandrungmangu 05 Berdasarkan Kerangka Asesmen Kompetensi Minimum (AKM) dan Faktor Internal-Eksternal - Dwi Novianti; Yuli Utanto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the numeracy competency of elementary school students and the factors that influence it as a basis for designing more effective and meaningful learning. The study used a quantitative approach with a case study design. The study population was all fifth-grade students of SDN Gandrungmangu 05, with a purposively selected sample of 6–9 students and 1 class teacher as a supporting informant. Data were collected through tests, interviews, observations, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that students' numeracy competency was categorized as high, medium, and low. Students with high competency were able to understand the context of the problem and use mathematical reasoning appropriately, while students in the medium and low categories still experienced difficulties in understanding reasoning-based problems and determining appropriate problem-solving strategies. The study also found that numeracy competency was influenced by internal factors such as learning motivation, learning interest, and cognitive abilities, as well as external factors such as teacher learning methods, family support, and the availability of learning facilities. These findings indicate that developing numeracy competency requires contextual learning support and collaboration between schools and families.